Safe and Sustainable Travel after COVID-19: The Case Study of Mueang Nan and Bang Saen Beach, Thailand - Satimanon , Monthien; Chunsom, Nada; Satimanon , Thasanee (Journal of Applied Economics and Management Strategy, 2025)
This study employs the open-ended Contingent Valuation Method (CVM) to assess willingness to pay (WTP) for a travel safety zone in Nan Old Town and Bang Saen Beach, Thailand, selected by the Department of Tourism, the Ministry of Tourism and Sport. The study consists of 406 samples using the convenience sampling method. Results reveal an average WTP of 200 baht (approximately 6 U.S. dollars), influenced by income, education, and travel expenses. The hypothetical aggregate WTP supports the potential extension of the program to other sites in Thailand. Despite the absence of entry fees, the program’s private benefits surpass its costs, with an aggregate WTP of 79 million baht compared to program costs of 15 million baht. The study suggests a favorable scenario for governmental investment in social benefits. Enhanced site quality and safety promises increased visitation, aiding sustainable tourism development. The program, crucial during crises like COVID-19, should remain adaptable for future challenges, fostering resilience through partnerships and community involvement. Promoting capacity building and operational sustainability aids long-term risk management in the tourism sector.